Biomimetic Gradient: A Microfluidic Model with Hydrogel Barriers for the Construction of Shear‐Free Attractive and Repulsive Cue Gradients (Adv. Mater. Technol. 2/2019). Issue 2 (8th February 2019) - Liu, Wenming; Han, Kai; Sun, Meilin; Huang, Zhongchao; Wang, Jinyi
Abstract : A microfluidic approach for the integration of multiple biochemical concentration gradients in a single microfluidic device is presented in article number1800434, by Wenming Liu, Jinyi Wang, and co‐workers. The employment of multidirectional hydrogel barriers permits a facile, stable, and long‐term microfluidic production of shear‐free single and double biochemical gradients. Multi‐gradient microfluidics provides a prototypical platform to perform on‐chip biomimetic neuronal manipulation and analysis for the exploration of neurogenesis and development as well as neuro‐regeneration.